Identitas Komunikasi Anggota Komunitas Dikaitkan Dengan Personaliti Merek Maxi Yamaha Di Kota Bandung - Valerian, Timotheus Adriel; Pamungkas, Indra Novianto Adibayu; Pramesthi, Jasmine Alya (eProceedings of Management, 2024)
This study focuses on studying communication identity for members of the MAXI Yamaha Bandung community. Theaim of this research is to understand perceptions about a motorized community in the city of Bandung. This researchis descriptive qualitative research using interview methods and literature study. This research looks at the activitiesof community members through the communication identities of their members. The results show that the existence ofculture and norms in a community shows the identity of that community. It is important for a community to make anagreement between members about what it wants to show to the community. Keywords-perception, community, identity, brand, motorized.